Pengaruh Store Atmosphetre dan Kualitas Produk terhadap Keputusan Pembelian Susu Murni Kaki Lima Setia Budi Medan - Ardana, Arya Dimas; Meutia, Riza Fanny; Amelia, Wan Rizca (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of Store Atmosphere and Product Quality on Purchasing Decisions among consumers of Setia Budi Street Pure Milk, Medan. This study used a quantitative approach with multiple linear regression analysis. The sample size was 90 respondents obtained through accidental sampling. Data collection was conducted through questionnaires.Partial test results indicate that Store Atmosphere has a positive and significant effect on Purchasing Decisions, with a calculated t-value of 6.420 > t-table 1.986 and a significance value of 0.000 < 0.05. Product Quality also has a positive and significant effect on Purchasing Decisions, with a calculated t-value of 4.270 > t-table 1.986 and a significance value of 0.000 < 0.05. The simultaneous test results indicate that Store Atmosphere and Product Quality jointly have a significant effect on Purchase Decisions, with a calculated F-value of 121.444 > F-table of 3.100 and a significance value of 0.000 < 0.05. The Adjusted R-square value of 0.721 indicates that 72.1% of the variation in Purchase Decisions can be explained by these two independent variables, while the remaining 27.9% is explained by other factors not examined in this study.Therefore, it can be concluded that a comfortable store atmosphere and good product quality play a significant role in driving consumer purchasing decisions. These findings can provide a strategic basis for businesses to increase customer satisfaction and loyalty.